THE EFFECT OF NANO BIOGLASS ON THE FABRICATION OF POROUS TITANIUM SCAFFOLDS - M. Ghavidel; S. M. Rabiee; M. Rajabi (Iranian Journal of Materials Science and Engineering, 2014)
In this study, porous titanium composites containing 5, 10 and 15 wt. % nanobioglass were fabricated by space holder sintering process. The pore morphology and phase constituents of the porous samples were characterized by X-ray diffractometry (XRD) and scanning electron microscopy (SEM). The mechanical properties were determined by compression test. The porosity of the sintered samples showed an upward trend with an increase in bioglass content. As the bioglass content was increased, the compressive strength was first increased and then decreased. The results obtained in this work suggest that the fabricated porous compact with 10 wt. % bioglass with compressive strength value of about 76.7 MPa, high porosity and good biocompatibility has the potential application for bone tissue engineering.